Ketahanan Galur Padi Hibrida Potensi Hasil Tinggi terhadap Penyakit Tungro - Ifa Manzila; Tri Puji Priyatno; Ida Hanarida (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
ABSTRACT Wild rice Oryza rufipogon accession can be used as a source of resistance genes to develop elite rice varieties for Rice tungro virus. This study aimed to examine some potential high yield rice lines developed by crossing IR64 with O. rufipogon for their response to three isolates of Rice tungro virus originating from Bogor, Sumedang, and Bali. Virus transmission was done by insect vector, Nephottetix virescens. Variation on plant response was observed. Three lines i.e. Bio5-AC-Blas/BLB, Bio62-AC-Blas/BLB-03, Bio111-BC-Pir7, showed stabile resistance response to all isolates of Rice tungro virus; 6 lines i.e. Bio132-AC2-Blas, Bio138-AC2-Blas, Bio148-Mamol-Dro, Bio154-Mamol-Dro, Bio159-Mamol-Dro, Bio 153-Mamol-Dro were moderately resistance. Virus isolates from Sumedang and Bali is more virulence than isolate from Bogor based on observation on incubation period, disease severity and suppression of plant height.